Akuntabilitas Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) Kecamatan Sukahening Kabupaten Tasikmalaya - Yeni Fitriani Somantri; Ulfa Luthfia Nanda (Universitas Pamulang, 2019)
This research aims to analyze of the accountability is managed by the Village Budget (APBDes). This research was conducted in 3 (three) villages within the Sukahening District of Tasikmalaya Regency, namely Calincing Village, Kiarajangkung Village, and Sundakerta Village. The research method uses a phenomenological approach and the type of qualitative research. The results of this study indicate that the accountability of village fund management in the District of Sukahening Tasikmalaya Regency has been carried out based on the principles of transparency, accountability, and participation. Reporting and accountability are generally carried out in accordance with the mechanism based on the provisions. The main obstacle or obstacle is the competency of management resources, so that there is still a need for ongoing assistance, training, supervision, and evaluation from the local government. Keywords: APBDes , Regional Financial Management, Accountability